Protozoal nodular dermatitis and panniculitis in a Rottweiler puppy caused by Caryospora bigenetica. Issue 1 (15th November 2015) - Tham, Heng L.; Linder, Keith E.; Tucker, Alison; Maggi, Ricardo; Bizikova, Petra
Abstract : Background: Caryospora bigenetica is an intracellular protozoan parasite in snakes and raptors (primary hosts) and rodents (secondary host). Experimental infection has been documented in mice, pigs and goats; natural infection in dogs is rare. Objectives: To describe the clinical presentation, histological features, treatment and outcome of a case of protozoal nodular dermatitis and panniculitis in a Rottweiler puppy caused by C. bigenetica . Results: The puppy presented with generalized subcutaneous nodules measuring up to 2 cm in diameter. Histopathology revealed marked suppurative to pyogranulomatous dermatitis and panniculitis with intralesional protozoal organism. PCR and DNA sequencing confirmed infection with C. bigenetica . Treatment with a combination of oral trimethoprim‐sulfamethoxazole (TMS), pyrimethamine and high‐dose clindamycin (20 mg/kg twice daily) resulted in resolution of lesions in 6 weeks. Discontinuation of the treatment 2 weeks later was followed by a rapid relapse of skin lesions. Clindamycin and TMS were restarted and all lesions resolved within 2 weeks; TMS was discontinued 4 weeks later due to adverse effects. The lesions remained in remission for 2 months while the puppy received clindamycin monotherapy before a second relapse of skin lesions occurred. Conclusion and clinical importance: To the best of the authors' knowledge, this is the first documentation of the treatment and outcome of C. bigenetica cutaneous infection in a dog. Although remission of clinical signs can be achieved with combination therapy of clindamycin and TMS, long‐term management is challenging and relapses should be anticipated. Abstract : Background – Caryospora bigenetica is an intracellular protozoan parasite in snakes and raptors (primary hosts) and rodents (secondary host). Experimental infection has been documented in mice, pigs and goats; natural infection in dogs is rare.Objectives – To describe the clinical presentation, histological features, treatment and outcome of a case of protozoal nodular dermatitis and panniculitis in a Rottweiler puppy caused by C. bigenetica .Conclusion and clinical importance – To the best of the authors' knowledge, this is the first documentation of the treatment and outcome of C. bigenetica cutaneous infection in a dog. Although remission of clinical signs can be achieved with combination therapy of clindamycin and TMS, long‐term management is challenging and relapses should be anticipated.